AEROALLERGENS (Curvularia, Nigrospora and Torula) IN A URBAN AREA OF VILLAHERMOSA, TABASCO, MEXICO - Cid Martínez, Marcela Alejandra; Hernández González, Jésus Ronaldo; Gaspar Génico, José Ángel (Kuxulkab’, 2022)
Curvularia, Nigrospora and Torula are fungi whose spores are dispersed in the air, due to the fact that they are produced in large quantities for the survival of the species, but due to their ontogenic properties, they are capable of triggering respiratory problems in some people, such as allergic rhinitis, which is why they are considered aeroallergens. The atmosphere of an urban area was monitored for a year with a sequential spore trap, but a month was considered for this work. To obtain the concentrations, that revised literature from the World Allergy Organization. A total of 2,238 spores m-3/air were obtained, in the month of study, seven days with concentrations above 100 spores m-3/air were recorded and a morning pattern from 5 to 11 hours was determined.